Pengaruh Lingkungan Pertemanan Terhadap Pergaulan Bebas Di Kalangan Mahasiswa Fakultas Ekonomi Universitas Negeri Medan - Sabrina Erisa Aulia Sihotang; Khairunnisa Umi Almas; Fais Irawan; Hapni Laila Siregar (Insan Zenius Ilmiah, 2026)
This study aims to analyze the influence of peer groups on promiscuity among students majoring in Economics Education. The college years are an important transitional phase during which students form their identities and expand their social networks. In this context, peers serve as significant sources of emotional support and behavioral references. However, intensive interaction with peers can also encourage individuals to engage in deviant behavior, such as promiscuity, which is often associated with premarital sex, alcohol consumption, and drug use. The research results indicate a positive and significant correlation between the peer environment and promiscuity, with a calculated t-value (10.055) exceeding the table t-value (1.69236) at a significance level of 0.000, which is less than 0.05. Each one percent increase in the peer environment contributes to a 1.153 increase in promiscuity, indicating that the higher the peer environment, the higher the promiscuity among students. The coefficient of determination of 0.754 indicates that the friendship environment can explain 75.4% of the variation in promiscuity. This study is supported by Bandura and Sutherland's theory, which explains that deviant behavior is learned through social interaction and observation of peer behavior. These findings emphasize the importance of understanding the dynamics of the peer environment in efforts to prevent promiscuous behavior among college students. Thus, this study is expected to provide insights for the development of effective intervention strategies to reduce promiscuous behavior on campus.